Theriogenology - Society for Theriogenology (Butterworth-Heinemann ; Elsevier Science, 1974)
"An international journal of animal reproduction."
Keywords: Theriogenology : Periodicals; Mammals : Reproduction : Periodicals; Reproduction : periodicals; Animals : periodicals; Reproduction; Animal Population Groups; Reproduction : Periodicals; Animal Population Groups : Periodicals; Thériogénologie : Périodiques; Mammifères : Reproduction : Périodiques; Mammals : Reproduction; Theriogenology